The Impact of Educational Leadership Styles on Teacher Productivity: A Comprehensive Review - Atif Nadeem; Saima Iram; Haseen Akhtar (Inverge Journal of Social Sciences, 2026)
Teacher productivity, teacher motivation, and effectiveness of the institutions are core elements that depend on educational leadership. This is a rigorous comprehensive literature review that summarizes 64 empirical studies that were published in 2016-2025 to explore the effects of different leadership styles on teacher productivity in learning institutions. Based on the PRISMA framework and quality assessment programs, we reviewed studies in K-12 and higher education settings. The results indicate that transformational leadership which involves visionary inspiration and mentorship as well as individualized consideration are associated to have the greatest effect on teacher productivity (b = 0.52-0.70), instructional leadership which is based on pedagogical support (b = 0.45-0.65) and democratic leadership based on collaboration (b = 0.40-0.55). Transactional leadership has a small short-term impact (b = 0.20-0.35) but is not sustainable whereas autocratic and laissez-faire leadership styles have negative implications on teacher performance. The most important mediating variables are job satisfaction, school climate, and professional development engagement. It is important to note that the effectiveness of leadership is heavily contextual such as the resources available in the school, the structure of governance, the cultural values and the socioeconomic context. Instead of adopting the single style, integrated, hybrid methods involving transformational vision, instructional expertise, and collaborative structures are more effective. The review marks out such crucial problems as the administrative overload, resource limitations, and the lack of preparedness among leaders. The main implications of the study to practitioners will be the creation of multifaceted leadership competence, instructional focus, positive school climate, and lifelong professional growth. The policymakers would need to enhance principal preparation, provide an environment where effective leadership can be achieved and align accountability and support development. Future studies ought to examine contextual moderators, implementation processes and long-term sustainability of leadership strategies. This review establishes that strategic educational leadership is one of the pillars of investment in enhancing teacher productivity and organizational performance. References Abbasi, S., Abbasi, P., Alvi, H., Murk, T., & Sajjad, R. (2025). The impact of leadership styles on teacher effectiveness: A study in Larkana schools. The Critical Review of Social Sciences Studies. https://doi.org/10.59075/08p39x93 Adriantoni, A., Komariah, A., Nurdin, D., & Herawan, E. (2023). The effect of transformational leadership and madrasah climate on elementary school teacher performance. Journal of Innovation in Educational and Cultural Research, 4(2). https://doi.org/10.46843/jiecr.v4i2.647 Ahmed, A. A. (2024). The impact of principal leadership styles on teachers’ job performance in primary schools. Human Nature Journal of Social Sciences. https://doi.org/10.71016/hnjss/rzk5dd68 Akullo, E. A., & Kamanyire, V. (2023). Head teacher leadership styles and teacher performance in primary schools in Kaabong District, Uganda. Journal of Education and Practice. https://doi.org/10.47941/jep.1182 Alzoraiki, M., Ahmad, A. R., Ateeq, A., & Milhem, M. (2024). The role of transformational leadership in enhancing school culture and teaching performance in Yemeni public schools. Frontiers in Education. https://doi.org/10.3389/feduc.2024.1413607 Andriadi, D., & Sulistiyo, U. (2024). The influence of transformational and instructional leadership styles of school principals on teachers’ performance, motivation, job satisfaction, and student achievement in primary and secondary schools. PPSDP International Journal of Education, 3(2). https://doi.org/10.59175/pijed.v3i2.335 Angwaomaodoko, & Anthony, E. (2023). The effect of leadership styles on teacher job satisfaction in Nigerian secondary schools. International Research in Education, 11(2). https://doi.org/10.5296/ire.v11i2.21012 Arina, Y., Revita, Y., Gistituati, N., & Rusdinal, R. (2023). The influence of principals’ participative leadership style and work climate on public middle school teacher performance. Edunesia: Jurnal Ilmiah Pendidikan, 4(3). https://doi.org/10.51276/edu.v4i3.487 As-Sadeq, H. A., & Khoury, G. (2006). Leadership styles in the Palestinian large-scale industrial enterprises. Journal of European Industrial Training. https://doi.org/10.1108/02621710610692043 Bhatti, N., Maitlo, G. M., Shaikh, N. A., Hashmi, M. A., & Shaikh, F. M. (2012). The impact of autocratic and democratic leadership style on job satisfaction. International Business Research, 5(2), 192–201. https://doi.org/10.5539/ibr.v5n2p192 Camatog, D. C., & Fu, X. (2024). Transforming leadership: Evaluating the impact of leadership styles on technical colleges in the National Capital Region, Philippines. International Multidisciplinary Research Journal. https://doi.org/10.54476/ioer-imrj/065077 Dahari, L. (2024). Adapting leadership: A literature review of effective management styles in modern educational settings. Sumy State University Journal. https://doi.org/10.21272/1817-9215.2024.2-04 Djumiastin, P., Muhimmah, H. A., & Subrata, H. (2025). Comparative study of leadership styles in public and private elementary schools. Al-Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 19(6). https://doi.org/10.35931/aq.v19i6.5691 Duran, C., & Barlas, P. J. (2025). Leading with impact: The relationship between school heads’ multifactor leadership styles and teachers’ job satisfaction in public secondary schools. British Journal of Teacher Education and Pedagogy, 4(6). https://doi.org/10.32996/bjtep.2025.4.6.1 Ed-Valsania, S., Lagua, A., & Moriano, J. A. (2022). Burnout: A review of theory and measurement. International Journal of Environmental Research and Public Health, 19(3), Article 1780. https://doi.org/10.3390/ijerph19031780 Guin, K. (2004). Chronic teacher turnover in urban elementary schools. Education Policy Analysis Archives, 12(42). https://doi.org/10.14507/epaa.v12n42.2004 Hadijah, N. (2024). The impact of leadership styles on teacher performance. Research Invention Journal of Law, Communication and Languages. https://doi.org/10.59298/rijlcl/2024/411318 Han, Y. (2025). The impact of leadership styles on effective education management. Forum for Linguistic Studies, 7(2). https://doi.org/10.30564/fls.v7i2.7839 Harianto, J. E., Umam, F. C., Ginanjar, F., Hidayat, Y., & Muiz, A. (2025). The impact of leadership styles on school performance: A comparative study of educational management models. International Journal for Science Review, 2(3). https://doi.org/10.71364/ijfsr.v2i3.23 Harsoyo, R. (2022). Bernard M. Bass’s transformational leadership theory and its application in improving the quality of Islamic educational institutions. Sajie: South Asian Journal of Islamic Education, 3(2). https://doi.org/10.21154/sajiem.v3i2.112 Hossen, B. (2024). Administrators’ leadership styles in Industrial Revolution 4.0 toward a proposed leadership educational model. International Multidisciplinary Research Journal. https://doi.org/10.54476/ioer-imrj/196274 Htun, S. S., Chakkaravarthy, M., & Bhaumik, A. (2025). Impact of emotional intelligence and leadership styles on employees’ job performance: A review paper. Journal of Multidisciplinary Research for SMET, 1(1). https://doi.org/10.64297/jmrsmet.v1i1.3 Hutasuhut, N. A., Simbolon, A. M. Y., Salsabilah, D., Siregar, R., & Siregar, S. A. (2025). The role of educational leadership in improving educational quality. Academia: Jurnal Inovasi Riset Akademik, 5(4). https://doi.org/10.51878/academia.v5i4.8226 Jaarsveld, L. V., Mentz, P. J., & Ellis, S. (2019). Implementing the multifactor leadership questionnaire (MLQ) in a challenging context. International Journal of Educational Management. https://doi.org/10.1108/IJEM-02-2018-0041 Joseph, C., & Sultana, M. (2025). Leadership styles of school heads and their impact on teacher performance: A qualitative study in private schools of District South Karachi. The Critical Review of Social Sciences Studies. https://doi.org/10.59075/qnfe3s74 Kairupan, D. (2023). Transactional and transformational leadership styles on the effectiveness of work from home and work productivity. Telaah Bisnis, 24(1). https://doi.org/10.35917/tb.v24i1.335 Khan, F. (2023). Transformational leadership and teacher work performance: Mediating effect of job autonomy and trust in school principal. Educational Management Administration & Leadership. https://doi.org/10.1177/17411432231172359 Lamja, D. (2024). Boosting teacher motivation and performance with transformational leadership in education. International Journal of Science and Research. https://doi.org/10.21275/SR24116024616 Marjono, F. K., & Heryjanto, A. (2023). The influence of the principal’s leadership style and school culture on teacher performance mediated by work motivation. Jurnal Indonesia Sosial Sains, 4(11). https://doi.org/10.59141/jiss.v4i11.923 Nadapdap, E., Laili, E. F., Natsir, M., & Setyadi, M. C. S. (2025). Exploring the influence of digital competence, work–life balance, and transformational leadership on teacher productivity through job satisfaction in rural educational contexts. East African Scholars Journal of Economics, Business and Management, 8(1). https://doi.org/10.36349/easjebm.2025.v08i01.006 Noor, S., Adnan, M., Rehman, L., & Shafiq, A. (2024). The impact of leadership styles on teacher self-efficacy and professional development. Bulletin of Business and Economics. https://doi.org/10.61506/01.00424 Novita, P., Cahya, Y. F., & Meilani, P. (2025). Reconstructing educational leadership theory: Building a holistic framework for 21st century schools. Feedforward Journal of Human Resource, 5(1). https://doi.org/10.19166/ff.v5i1.9577 Pacia, D. R., & Guevarra, P. M. (2023). Influence of path–goal theory of leadership styles and the moderating role of task structure on teachers’ satisfaction, motivation, and performance. International Journal of Multidisciplinary Applied Business and Education Research, 4(7). https://doi.org/10.11594/ijmaber.04.07.15 Pallangyo, H., & Mwila, P. (2025). Leadership styles and teacher job performance: Enhancing productivity in Tanzanian secondary schools. Global Journal of Basic Education, 1(1). https://doi.org/10.61227/gjbe.v1i1.169 Pitriani, E. (2024). Educational leadership in improving school performance and teacher professional development: A literature review. PPSDP International Journal of Education, 3(2). https://doi.org/10.59175/pijed.v3i2.312 Puspitadani, E., Yudea, F., & Loo, F. (2022). Educational leadership and learning quality: The influence of the principal’s leadership style on teacher performance. Jurnal Ilmu Pendidikan dan Humaniora, 11(3). https://doi.org/10.35335/jiph.v11i3.24 Rafiq-uz-Zaman, M. (2023). Analysis of leadership styles and decision-making effectiveness in public sector universities in Pakistan: A systematic review. Inverge Journal of Social Sciences, 2(1), 72–91. https://doi.org/10.63544/ijss.v2i1.209 Rafiq-uz-Zaman, M. (2025). Unpacking the leadership and governance crisis in Pakistani universities: Structural, political, and institutional drivers. The Critical Review of Social Sciences Studies, 3(4), 901–912. https://doi.org/10.59075/pk8zan95 Rafiq-uz-Zaman, M., Bano, S., & Naveed, Y. (2025). Comparative analysis of authoritative and democratic leadership styles and their impact on school management effectiveness. Inverge Journal of Social Sciences, 4(2), 105–117. https://doi.org/10.63544/ijss.v4i2.132 Romy, E. (2024). Examining the impact of leadership approach and principal’s drive on educator productivity. Jurnal Ekonomi, Bisnis & Entrepreneurship. https://doi.org/10.55208/bzq06z82 Saepurohman, L., & Satori, D. (2021). The effect of servant leadership on teacher performance. Advances in Social Science, Education and Humanities Research. https://doi.org/10.2991/assehr.k.210212.040 Sarah, M., Bariham, I., & Quansah, J. Y. D. (2023). Impact of headteachers’ leadership styles on teachers’ job performance in Sagnarigu Municipality, Ghana. Social Education Research. https://doi.org/10.37256/ser.4220232903 Sari, N., Ilham, D., Hasbi, H., & Mardhiah, M. (2025). The role of leadership styles in improving educational standards. International Journal of Asian Education, 6(1). https://doi.org/10.46966/ijae.v6i1.467 Sarwar, U., Tariq, R., & Yong, Q. Z. (2022). Principals’ leadership styles and their impact on teachers’ performance at college level. Frontiers in Psychology. https://doi.org/10.3389/fpsyg.2022.919693 Sitiol, D. L., Mwamba, G., & Kobuthi, E. N. (2025). Head teachers’ leadership styles and pupils’ KCPE performance: A case study of Imaroro Ward, Kenya. Human Resource and Leadership, 5(1), 62–79. https://doi.org/10.70619/vol5iss1pp62-79 Sugiyanto, H. (2025). Leadership styles, quality of education, and educational institution management: A systematic review from a sustainable education perspective. Journal Corner of Education Linguistics and Literature, 4(3). https://doi.org/10.54012/jcell.v4i3.423 Sultana, N., Ayoob, M., Samson, H., & Saeed, A. (2024). Exploring how transformational leadership styles impact educational environments and students. Bulletin of Business and Economics. https://doi.org/10.61506/01.00530 Sundari, S., Suwito, S., & Wibowo, E. (2023). Analysis of school-based management and principal leadership in improving teacher performance. Journal of Innovation in Teaching and Instructional Media, 3(2). https://doi.org/10.52690/jitim.v3i2.708 Sustiyatik, E. (2023). The dual pillars of academic excellence: Transformational leadership and organizational commitment. Journal of Innovation in Business and Economics, 7(1). https://doi.org/10.22219/jibe.v7i01.28221 Sutisna, A., Khoriah, A., Juhartono, & Norman, E. (2024). Transformational leadership and team synergy in improving communication and collaboration in educational settings. Media Ekonomi dan Manajemen, 3(3). https://doi.org/10.56709/mesman.v3i3.551 Twumasi, C., Partey, P. A., & Adom, D. (2025). The impact of leadership styles on selected educational administrators in Ghana. E-Journal of Humanities, Arts and Social Sciences. https://doi.org/10.38159/ehass.202561223 Wu, H. W. W. B. (2025). The leadership style of principals in teacher effectiveness: An exploratory study. Transformative Pedagogies. https://doi.org/10.64229/33mcpj39